Distributed Relay-Assisted Retransmission Scheme for Wireless Home Networks. (28th April 2014) - Park, Seunghyun; Park, Hyunhee; Kim, Eui-Jik
Abstract : A relay transmission is a promising technology to improve network performance in dynamic infrastructure. In this paper, we propose a distributed relay-assisted retransmission (DRR) scheme in multirate wireless home networks. The idea is to exploit overhearing nodes to retransmit on behalf of sender node after receiving the block acknowledgement (B-ACK) from destination node. For the first transmission, a basic relay (BR) node is used by considering the high data rate between source node and BR node. And then, for the retransmission, a retransmission relay (RR) node is used by considering the high data rate between RR node and destination node. The DRR scheme extends a distributed reservation protocol in WiMedia home networks and inquires the candidate relay node as BR nodes and RR nodes during beacon period. In addition, the DRR scheme can minimize control overhead for relay transmission because all nodes should send and listen to the beacon frames of neighbor nodes during beacon period. We also present the relay decision scheme and channel allocation procedure for maximizing the efficiency in the DRR scheme. Extensive simulation results demonstrate that the DRR scheme can improve the overall throughput by 40% and reduce the energy consumption by 47% compared with nonrelay transmission schemes when the number of nodes increases.